Development of competitive advantages for tiger prawn breeding business actors in Muara Badak, Kutai Kartanegara Regency, as an optimization of strengthening the coastal gender economy - Arditiya Arditiya; Euis Happy Wangloan; Agus Rony Katili; Bambang Tri Murtiono; Anisah Azizah (Universitas Muhammadiyah Magelang, 2022)
Indonesia is an archipelagic country with a strategic plan for the development of a maritime-based economic sector that is integrated with blue economy principles. Improving the quality of life of coastal communities is a central issue of sustainable development. Tiger prawn breeding is a competitive advantage for coastal communities through hatchery and marketing of export quality seeds. The low level of understanding of coastal communities in the management of tiger shrimp culture has an impact on the climate of business independence, so this is also a focus of problems in community partnership service activities. Optimizing the role of women as a representative of the coastal gender economy is a novelty goal and value that must be achieved in order to realize the ideals of a blue economy that supports national economic development through the maritime sector. The development of competitive advantage in Muara Badak Subdistrict, Kukar Regency is carried out using pre-activity input methods, activity processes, outputs and mentoring evaluations to strengthen family and business financial literacy, marketing management, to provide stimulation in the form of strategies in dealing with the threat of export failure and others. The result of the program is an increase in the capability of tiger prawn breeding business actors in Muara Badak District, Kutai Kartanegara Regency.